Identification of Arp2/3 Complex Subunits as Prognostic Biomarkers for Hepatocellular Carcinoma - Huang, Shenglan; Li, Dan; Zhuang, LingLing; Sun, Liying; Wu, Jianbing (Frontiers in Molecular Biosciences, 2021)
The actin-related protein 2/3 complex (Arp2/3) is a major actin nucleator that has been widely reported and play an important role in promoting the migration and invasion of various cancers. However, the expression patterns and prognostic values of Arp2/3 subunits in hepatocellular carcinoma (HCC) remain unclear. In this study, The Cancer Genome Atlas (TCGA) and UCSC Xena databases were used to obtain mRNA expression and corresponding clinical information, respectively. The differential expression and Arp2/3 subunits in HCC were analyzed by “limma” package of R 4.0.4 software. The prognostic value of each subunit was evaluated using Kaplan-Meier survival analysis and Cox proportional hazards regression analyses. The results revealed that mRNA expression of Arp2/3 members (ACTR2, ACTR3, ARPC1A, APRC1B, ARPC2, ARPC3, ARPC4, ARPC5, and ARPC5L) was upregulated in HCC. Higher expression of Arp2/3 members was significantly correlated with worse overall survival (OS) and shorter progression-free survival (PFS) in HCC patients. Cox proportional hazards regression analyses demonstrated that ACTR3, ARPC2, and ARPC5 were independent prognostic biomarkers of survival in patients with HCC. The relevance between tumor immunocyte infiltration and the prognostic subunits was determined using the TIMER 2.0 platform and GEPIA database. Gene set enrichment analysis (GSEA) was performed to explore the potential mechanisms of prognostic subunits in the carcinogenesis of HCC. The results revealed that ACTR3, ARPC2, and ARPC5 were significantly positively correlated with the infiltration of immune cells in HCC. The GSEA results indicated that ACTR3, ARPC2, and ARPC5 are involved in multiple cancer-related pathways that promote the development of HCC. In brief, various analyses indicated that Arp2/3 complex subunits were significantly upregulated and predicted worse survival in HCC, and found that ACTR3, ARPC2, and ARPC5 could be used as independent predictors of survival and might be applied as promising molecular targets for diagnosis and therapy of HCC in the future.